Knowledge and perception of users on roles of internal medicine specialty and medical internists - Romaní-Romaní, Franco (2009)
Introduction: Internal medicine specialty is challenged in remaining competitive in the complex health system. Low public awareness of the capabilities and competence of the internists is one of these challenges. Objectives: To determine patients’ knowledge and perceptions on both internal medicine and medical internist roles. Design: Transversal, descriptive and analytical study. Settings: Arzobispo Loayza Hospital, Edgardo Rebagliati Hospital, and a private clinic. Participants: Adult patients attended at the three hospitals’ internal medicine services. Interventions: The patients solved a self-administered and anonymous questionnaire in September 1-15, 2008. Main outcomes measures: Level of knowledge on internal medicine and internists and perception of confidence. Results: Five hundred patients answered the questionnaire, 42,8% at Loayza Hospital, 40% at Rebagliati Hospital, and 17,2% at a private clinic. Only 12,2% had an adequate level of knowledge; 79% of patients demonstrated confidence in the internist’s ability to treat symptoms, 50,2% showed confidence in the internist for performing clinical examination and 45,9% in the internist treating specific diseases. Conclusions: Patients do not have a clear definition on internal medicine and the role of internists. Therefore, efforts should consider public education on this topic in order to promote better understanding of the internist’s role as a specialist in adult medicine.